Using segmental isotope analysis of teleost fish vertebrae to estimate trophic discrimination factors of bone collagen1. (19th December 2018) - Matsubayashi, Jun; Umezawa, Yu; Matsuyama, Michiya; Kawabe, Ryo; Mei, Weiping; Wan, Xin; Shimomae, Atsushi; Tayasu, Ichiro
Abstract: We conducted feeding experiments with sardine ( Sardinops melanostictus ) and Japanese flounder ( Paralichthys olivaceus ) to investigate trophic discrimination factors (TDFs) in bone collagen using retrospective isotope analysis. Sardines and Japanese flounder were fed a single diet for 9 months and 4 months, respectively. At the end of the experiments, we extracted vertebral centra from six sardines and seven Japanese flounder and subdivided them into multiple sections. We extracted bone collagen from each section, and measured the δ 13 C and δ 15 N of each vertebral section and food source. In all fish samples, the δ 13 C and δ 15 N values of bone collagen increased from the centers of vertebrae to the marginal sections. This trend was consistent with the predicted isotopic shift in the diets of these fishes. The TDFs for sardines were estimated at 5.58 ± 0.25‰ (mean ± SD) for δ 13 C and −0.70 ± 0.25‰ for δ 15 N; those for Japanese flounder were 3.89 ± 0.14‰ for δ 13 C and 1.18 ± 0.35‰ for δ 15 N. Our results show that segmental analysis of vertebrae can reconstruct δ 13 C and δ 15 N values for multiple life‐stages of both fish species and is useful for estimating TDFs and turnover times of fish bone collagen.